Efektivitas Program Pelatihan Kerja Di BLK Disnakertrans Kabupaten Karawang - Dicky Sulistiya Harta Wijaya; Syifa Pramudita Faddila (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Job Training Centers are government agencies that organize job training programs, trial training programs, competency tests and empowerment training institutions in industrial sector. The training held is Competency-Based Training by opening several areas of competence needed in the industrial sector. The effectiveness of program training on resource allocation activities is right on target and programmed by government as a public servant as a form of investment in the form of a skilled workforce, competitive workforce and competent workforce by increasing their capabilities programmatically through training institutions or Vocational Training Centers. This study used a qualitative research method, the data used were primary data obtained from interviews with employees and participants at BLK Karawang district and secondary data obtained from agencies related to research. The results of the study show that this job training program is very effective in reducing unemployment rates in Karawang district, there are several aspects that are considered low and need improvement in the level of satisfaction to be training on aspects of participant reactions. To increase the effectiveness of the training program, it is necessary to improve the quality of services at the center, and the placement of workers because the number of placements after training is still low, and then cooperation with stakeholders is still limited.